Perceived Barriers to Utilizing Maternal and Neonatal Health Services in Contracted-Out Versus Government-Managed Health Facilities in the Rural Districts of Pakistan - Atif Riaz; Shehla Zaidi; Asif Raza Khowaja (Kerman University of Medical Sciences, 2015)
Background A number of developing countries have contracted out public health facilities to the Non-Government Organizations (NGOs) in order to improve service utilization. However, there is a paucity of in-depth qualitative information on barriers to access services as a result of contracting from service users' perspective. The objective of this study was to explore perceived barriers to utilizing Maternal and Neonatal Health (MNH) services, in health facilities contracted out by government to NGO for service provision versus in those which are managed by government (non-contracted). Methods A community-based qualitative exploratory study was conducted between April to September 2012 at two contracted-out and four matched non-contracted primary healthcare facilities in Thatta and Chitral, rural districts of Pakistan. Using semi-structured guide, the data were collected through thirty-six Focus Group Discussions (FGDs) conducted with mothers and their spouses in the catchment areas of selected facilities. Thematic analysis was performed using NVivo version 10.0 in which themes and sub-themes emerged. Results Key barriers reported in contracted sites included physical distance, user charges and familial influences. Whereas, poor functionality of health centres was the main barrier for non-contracted sites with other issues being comparatively less salient. Decision-making patterns for participants of both catchments were largely similar. Spouses and mother-in-laws particularly influenced the decision to utilize health facilities. Conclusion Contracting out of health facility reduces supply side barriers to MNH services for the community served but distance, user charges and low awareness remain significant barriers. Contracting needs to be accompanied by measures for transportation in remote settings, oversight on user fee charges by contractor, and strong communitybased behavior change strategies.